Enabling multilingual domain names: addressing the challenges of the Arabic script top-level domains. Issue 1 (2nd January 2016) - Hussain, Sarmad; Bakhat, Ahmed; Benamar, Nabil; Mumin, Meikal; Ullah, Inam
ABSTRACT: Domain names are a key to accessing content online. Even though much of the content is multilingual now, the domain names are still mostly limited to Latin characters. The paper focuses on the top-level domains, as a part of the Domain Name System (DNS), and explains the community-driven effort to make these multilingual using the internationalized domain name framework. The case of Arabic script is presented, highlighting the challenges faced for the script community in developing specific rules and recommendations to ensure the validity and uniqueness of labels for the DNS Root zone. The paper highlights the tension between enabling broadest expression with the domain names to facilitate the linguistic community while simultaneously adhering to the conservative procedure set out by the technical community to ensure the security and stability of the Root zone. The paper finally presents the details and evaluation of the proposed solution for the top-level domain names in Arabic script, addressing the end-user needs while minimizing the end-user confusion.